Consumer Protection under Directive 2015/2366 on Payment Services in the Internal Market – Selected Issues - Byrski, Jan (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
Directive 2007/64 on payment services (PSD 1) introduced protection for consumers of payment services. First and foremost, the consumer should receive the basic information required by law before and after the execution of a payment. Secondly, the consumer is made more familiar with the charges incurred when paying in shops, including online shops. Third, PSD 1 provided the protection of consumer rights in the event of unauthorised or incorrect charges to the consumer’s payment account. Fourthly, within PSD 1 the market for payment systems was opened, thus allowing entities other than banks to provide payment services. In order to protect consumers’ money, these new institutions have become subject to regulation (supervision). The European Union legislator, when establishing a new framework for the provision of payment services in the European Union (PSD 2), reached the conclusion that existing protection for the consumer – the payment service user, was insufficient. Therefore, new legal instruments protecting the consumer have been introduced. However, upon examination a conclusion has been reached that while some of the protections should be accepted, others warrant critical review.